الطباق في سورة النحل (دراسة تحليلية بلاغية) - Burhan Lukman Syah (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2023)
AbstrackIbrahim Abdullah Rafidah said in his book that the Qur’an is the first of the principles of grammar. Thus, he determined the correct history of the relationship of grammatical research with the Holy Qur’an as an existing and close link since the beginning of thinking about inventing grammar and building its edifice. Hence, every person needs to learn the Arabic language to understand the meanings of the Qur'an. The Arabic language has been integrated not only through the science of grammar, but also has a strong relationship with it, which is the science of rhetoric to know the meanings of the verses of the Qur’an and the miraculous rhetorical methods. Thus, the appropriate study for this field is the rhetorical analytical study. After the researcher perused the enlightening book of tafsir Al-Munir, the researcher found Surah An-Nahl, which mentioned the divine power in this universe, the evidence and the oneness of God. There are two opposite words whose meaning is unknown. Therefore, this research is related to At-Tibaq in Surat An-Nahl and its revelation. The researcher used in his research is qualitative desk research. The method of data collection used by the researcher is the Documentary Method. An approach that uses written sources to obtain data, The result of this research: The number of verses matching in Surat An-Nahl is thirteen verses: 6, 17, 19, 36, 37, 48, 61, 75, 80, 83, 93, 96, 103, 116. As for the meanings of Al-Tibaq in Surat Al-Nahl, it can be relied on the interpretation of the written verse in the analysis, as well as on the images of the written dishes for which the dishes are cast from the real and figurative dishes.